Effectiveness of Video Education in Preventing Electric Smoking Behavior in Students - Sunarti, Sri; Bin Ahmad Fauzi, Fatimah; Nur Azizah, Lili; Amalia, Nida (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2024)
Electronic cigarettes have experienced very rapid development, recently many people have been seen using electronic cigarettes, In Indonesia, as many as 2.1 million who use electronic cigarettes are students. Control of electronic cigarettes is carried out by providing education to change the knowledge and attitudes of adolescents. In the digital era, innovation is possible in delivering messages for prevention through audiovisual media such as short videos. This study aims to determine the effectiveness of video media on knowledge, attitudes and actions of electronic smoking behavior in adolescents at SMK Istiqomah Muhammadiyah 4 Samarinda. This study was conducted using an Experimental research method with a pre and post design approach. This study involved two research groups, namely the experimental group and the control group. Data were obtained using a questionnaire on knowledge, attitudes and actions of electronic smoking. The research sample was 234 students. The sampling technique that will be used in this study is Simple Random Sampling. Statistical Wilcoxon Signed Rank Test. The results of the study were that after education using video there was an increase in knowledge of 5 points and attitudes of 2 points. The results of the statistical test showed that there was an effect of video education on knowledge and attitudes with a P Value of 0.000. The conclusion of this study is that video education about the dangers of electronic cigarettes can increase knowledge and attitudes towards preventing electronic smoking behavior.